Abstract Bochner and McShane integrals - Schwabik, Štefan (Annales Mathematicae Silesianae, 1996)
A short description of the classical Bochner integral is presented together with the McShane concept of integration based on Riemann type integral sums. The corresponding classes are compared and it will be shown that the situation is different for finite- and infinite- dimensional valued vector functions.